A retrospective study of patients treated with by oral anticancer drugs: Impact of pharmacy consultation. Issue 4 (7th October 2022) - Clou, Emmanuelle; Dubois, Antonin; Gaudas, Julien; Palisson, Hugo; Chetouane, Kahina; Talarmin, Chloé; Meynial, Olivia; Nguyen, Jacqueline; Assoun, Sandra; Benderra, Marc-Antoine; Nasrallah, Dhekra; Esteso, Adoraction; et al.
Abstract: Introduction: Pharmacists can contribute to improve prevention and management of patients treated with oral anticancer drugs. The aim of this study was to describe pharmacist interventions in drug-related problems (DRPs), medication optimization, and patient management. Methods: The pharmaceutical process allows obtaining exhaustive list of usual patient treatment, patient education, and telephonic follow-up at home. During pharmacy consultation and telephonic follow-up, the number and type of pharmacist interventions were collected and classified into 3 categories: DRPs, medication optimization, and patient management. During telephonic follow-up, pharmacists detected adverse events. Results: From February 2016 to May 2020, 224 pharmacy consultations were conducted. A total of 508 pharmacist interventions (248 for pharmacy consultation and 260 for telephonic follow-up) were conducted, with an average of 2.3 pharmacist interventions per patient. Pharmacist interventions were 44.4% for patient management, 29.6% for DRPs, and 26.0% for medication optimization. After pharmacy consultation, 36.2% of patients' usual treatments were amended. Two hundred thirteen adverse events (AEs) were reported, and 38.8% of patients had one or more AEs. AEs detected were 15 for temporary discontinuation of oral anticancer drugs, 25 for emergency consultations, and 3 for hospitalizations. Conclusion: Pharmacy consultation has shown that pharmacists can contribute to optimize medicinal care for patients with cancer.